Design and Synthesis of Novel Cyclic Indole Amides for Versatile Biological Applications - Hamilton, Alexander John (Curtin University, 2024)
Indoles are a widely utilised chemotype in nature and medicinal chemistry, in which several of these compounds are cyclic or contain amide functionalisation. This thesis describes the exploration and synthesis of conformationally restricted, cyclic indole amides and their versatile biological applications. Several synthetic routes and techniques were utilised to produce over 85 novel compounds with selected final compounds biologically assessed as cannabinoid ligands, antitumour agents and antiplasmodial compounds.